THE INFLUENCE OF STORYTELLING MARKETING ON CONSUMER PURCHASE INTENTION THROUGH EMOTIONAL BRANDING AS A MEDIATING VARIABLE (STUDY AT RUMAH MAKAN JUKU EJA IN SIWA, WAJO REGENCY) - Muhammad Anugrah Ardhana; Nurhuda Nurhuda; Ersya Kallang; Sarmila Jamaluddin; Delpin Delpin (Jurnal Manajemen Dan Bisnis, 2026)
This study aims to analyze the influence of Storytelling Marketing and Emotional branding on consumer purchase intention at Rumah Makan Juku Eja in Siwa, Wajo Regency. Specifically, it seeks to determine the influence of Storytelling Marketing on Emotional branding, the influence of Storytelling Marketing on consumer purchase intention, and the influence of Emotional branding on consumer purchase intention. A quantitative method was employed using path analysis with the assistance of SPSS software. The sample consisted of 65 consumers of Rumah Makan Juku Eja, selected through non-probability sampling with a purposive sampling technique. Data were collected using a Likert-scale questionnaire consisting of 24 statement items covering 13 indicators. The results show that Storytelling Marketing has a positive and significant effect on Emotional branding. Individually, Storytelling Marketing has no significant effect on consumer purchase intention, whereas Emotional branding has a positive and significant effect on consumer purchase intention. These results indicate that Storytelling Marketing affects consumer purchase intention indirectly through Emotional branding as a full mediating variable.